Commissural NTS lesions enhance the pressor response to central cholinergic and adrenergic activation - Vieira, Alexandre A. [UNESP] (2012)
Electrolytic lesions of the commissural nucleus of the solitary tract (commNTS) in rats enhance the pressor response to bilateral carotid occlusion or to intravenous infusion of hypertonic NaCl without changing baroreflex responses. In an opposite direction, commNTS lesions abolish the pressor responses to peripheral chemoreflex activation. These opposite effects of commNTS lesions apparently result from an impairment of sympathetic activation in one case and in a facilitation of vasopressin secretion in the others. In the present study, we investigated the effects of the electrolytic lesions of the commNTS in the pressor responses that depend on sympathetic activation and vasopressin secretion produced by central cholinergic or adrenergic activation with intracerebroventricular (i.c.v.) injections of carbachol or noradrenaline, respectively, in unanesthetized rats. Male Holtzman rats (280-320g, n = 8-15/group) with acute (1 day) or chronic (21 days) sham or commNTS lesions (1 mA x 10 s) and a stainless steel cannula implanted in the lateral ventricle were used. Acute commNTS lesions increased the pressor response to i.c.v, injection of carbachol (0.5 nmol/1 mu 1) (52 +/- 2, vs. sham: 37 +/- 2 mmHg) or noradrenaline (80 nmol/1 mu 1) (45 +/- 6, vs. sham: 30 +/- 3 mmHg), whereas chronic commNTS lesions did not affect the pressor responses to the same treatments. Lesions of the commNTS impaired chemoreflex responses produced by intravenous KCN, without changing baroreflex responses. The results suggest that commNTS-dependent inhibitory signals are involved in the modulation of the pressor responses to central cholinergic and adrenergic activation, probably limiting vasopressin secretion. (C) 2012 Elsevier B.V. All rights reserved.